DETERMINANT ANALYSIS OF NET PROFIT MARGIN USING BANK-SPECIFIC VARIABLES OF ISLAMIC BANKS IN INDONESIA - Ramadhan, Dary Rahmat; Anggono, Achmad Herlanto (Journal of Business and Management, 2018)
Abstract - The financial sector strongly influences economic growth in a country. The role of banks here is vital as an intermediary for exchanging money in the community. In conducting its operational activities, the bank focuses its business activities as a manager of public funds as its primary business activity. Besides, to be used to generate profits for banks, interest rates also function as a tool to influence a country's economy. Indonesia adopted a dual banking system, namely a conventional bank that runs a regular system and Islamic banks that use Islamic law as a basis for its operational activities. Islamic Banks provide a profit-sharing system from profits derived from funds managed in exchange for interest. To calculate the performance of Islamic banks to generate profit, the Net Profit Margin Ratio. This study obtained data from the website of the Financial Services Authority (OJK) and from official websites of each bank which included 7 Islamic banks which belonged to the category of foreign exchange Islamic banks and mixed Islamic banks which took place in 2011 the first quarter to 2017 fourth quarter. Regression results show that four of the six independent variables, namely Bank Size, Deposit and Short Term Financing to Total Asset, Operating Expense to Operating Income Ratio, and Capital Adequacy Ratio have a significant impact on Net Profit Margin. While Financial to Deposit Ratio and Credit Risk have no significant effect on Net Profit Margin. This study has recommendations to stakeholders in the banking industry pay more attention to these variables to adjust the value of Net Profit Margin. From the results of the intercept shows Panin Dubai Syariah Bank must pay attention to their Net Profit Margin because it has the lowest intercept from other banks. Keywords: Islamic Banking, Banking Industry, Profit Margin, Profitability, Regression